Administration of a Histone Deacetylase Inhibitor into the Basolateral Amygdala Enhances Memory Consolidation, Delays Extinction, and Increases Hippocampal BDNF Levels - Valiati, Fernanda E.; Vasconcelos, Mailton; Lichtenfels, Martina; Petry, Fernanda S.; de Almeida, Rosa M. M.; Schwartsmann, Gilberto; Schröder, Nadja; de Farias, Caroline B.; Roesler, Rafael (Frontiers in Pharmacology, 2017)
Gene expression related to the formation and modification of memories is regulated epigenetically by chromatin remodeling through histone acetylation. Memory formation and extinction can be enhanced by treatment with inhibitors of histone deacetylases (HDACs). The basolateral amygdala (BLA) is a brain area critically involved in regulating memory for inhibitory avoidance (IA). However, previous studies have not examined the effects of HDAC inhibition in the amygdala on memory for IA. Here we show that infusion of an HDAC inhibitor (HDACi), trichostatin A (TSA), into the BLA, enhanced consolidation of IA memory in rats when given at 1.5, 3, or 6 h posttraining, but not when the drug was infused immediately after training. In addition, intra-BLA administration of TSA immediately after retrieval delayed extinction learning. Moreover, we show that intra-BLA TSA in rats given IA training increased the levels of brain-derived neurotrophic factor in the dorsal hippocampus, but not in the BLA itself. These findings reveal novel aspects of the regulation of fear memory by epigenetic mechanisms in the amygdala.